Exigências nutricionais de ovelhas gestantes da raça Santa Inês - Gilberto de Lima Macedo Junior (2008)
This study was conducted in the Zootechnics Department of Veterinary School in Animal Metabolism and Calorimetric Laboratory dependencies, witch aimed to evaluate pregnancy uterus chemical composition and yours respectively compounds. 72 ewes were used at different pregnancy period, with different fetus numbers and 10 non-pregnant ewes, all of Santa Ines breed. Animals were submitted or not to food restrictions. Ewes were housed in metabolic cages with water and salt trough, timber floor and funnel to collect feces and urine with screens side to avoid feces loss. Animal’s nutritional requirements were calculated from the NRC (1985), following the recommendations predicted to dry matter intake, energy (in total digestible nutrients, TDN) and crude protein (CP). For animal group on food restriction was removed 15% of requirements in energy (TDN) and crude protein. Maize meal (Zea mays), soybean meal (Glycine max), chopped Tifton hay (Cynodon spp.) and limestone composed ewes diet. Mineral salt was offered ad libtum to animals, being specific to sheep (Vacci-Phos, Vaccinar ®). Animal sacrifice process followed the recommendations made by the UFMG ethics committee on animal experiments, protocol 77/2006, valid until 20/09/2011. Nutritional restriction does not alter pregnancy development. It is possible; there is a mechanism which controls nutrients partition between ewes and pregnant uterus, because it was not changed by nutritional management. Energy and protein restriction cause reduction in fat and minerals amount of fetus. Mammary gland development is highly dependent on nutrition, fetuses number pregnancy stage. Nutritional management, fetuses number and pregnancy stage alter uterus empty composition and uterine fluids. Keywords: Chemical, energy, nutrition, ovine, protein